New insights into the vibrational and optical signatures of trans-stilbene via integrated experimental and quantum mechanical approaches. Issue 28 (4th July 2016) - Massuyeau, Florian; Faulques, Eric; Latouche, Camille; Barone, Vincenzo
Abstract : The structure, spectroscopic parameters and optical properties of stilbene have been investigated by a computational protocol including suitable treatment of anharmonic contributions together with new experimental results. Abstract : The structure, spectroscopic parameters and optical properties of stilbene have been investigated by a computational protocol including suitable treatment of anharmonic contributions together with new experimental results. A full reproduction of the 500–3500 cm −1 IR spectrum has been possible using the VPT2 approach and new insights are provided in the 6000 cm −1 region where typical signatures have been characterized as a set of overtones and combination bands. Vibrational contributions to electronic transitions have been taken into account to simulate the optical (absorption and emission) properties of stilbene. Spectra simulated by employing the state-of-the-art Adiabatic Hessian model coupled to global hybrid functionals are in remarkable agreement with their experimental counterparts and the inclusion of Herzberg–Teller contributions further improves the results with respect to those delivered by the basic Franck–Condon model.